2023
DOI: 10.1093/nar/gkac1231
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of Qng1-mediated salvage of the micronutrient queuine from queuosine-5′-monophosphate as the biological substrate

Abstract: Eukaryotic life benefits from—and ofttimes critically relies upon—the de novo biosynthesis and supply of vitamins and micronutrients from bacteria. The micronutrient queuosine (Q), derived from diet and/or the gut microbiome, is used as a source of the nucleobase queuine, which once incorporated into the anticodon of tRNA contributes to translational efficiency and accuracy. Here, we report high-resolution, substrate-bound crystal structures of the Sphaerobacter thermophilus queuine salvage protein Qng1 (forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The described LC-MS/MS method employed here has been successfully applied by our research group to quantify preQ1, Q-5'MP, Q-3'MP, q and Q in the intracellular extracts and culture medium (9). However, human blood is a more complex matrix, containing high levels of phospholipids, with implications for ion suppression or enhancement in LC-MS/MS analyses (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The described LC-MS/MS method employed here has been successfully applied by our research group to quantify preQ1, Q-5'MP, Q-3'MP, q and Q in the intracellular extracts and culture medium (9). However, human blood is a more complex matrix, containing high levels of phospholipids, with implications for ion suppression or enhancement in LC-MS/MS analyses (29).…”
Section: Discussionmentioning
confidence: 99%
“…Humans obtain Q as a micronutrient from diet or gut microflora. An enzyme called QNG1 (previously known as DUF2914) hydrolyses Q or a Q monophosphate to release queuine (q), which in turn can be salvaged and reincorporated into tRNA by the eukaryotic tRNA guanine transglycosylase (eTGT) which is comprised of the QTRT1 and QTRT2 subunits (9).…”
Section: Introductionmentioning
confidence: 99%
“…Both APB‐coupled Northern blotting and LC–MS/MS analyses revealed that Q is present in all tissues, with heart, skeletal muscle, and brain containing the highest Q levels, whereas spleen has one of the lowest Q‐tRNA levels as described previously (Thumbs et al , 2020 ). Even though differences in tissue‐specific Q‐tRNA content can be explained by differences in tissue turnover rate (Spalding et al , 2005 ), salvage of the micronutrient queuine (Hung et al , 2023 ), and, to some extent, by changes in the expression of the Qtrt1 gene (Appendix Fig S1D ), the molecular mechanism behind these differences is still not fully explored. One may speculate that an adaptation between Q‐tRNA modification level and tissue‐specific codon usage, as previously described for Drosophila developmental stages (Zaborske et al , 2014 ), may be the driving force.…”
Section: Discussionmentioning
confidence: 99%
“…Two, QueK and Qng1, have been experimentally characterized thus far. These enzymes are members of unrelated protein families and harbor different substrate specificities ( Figure 1 and [ 7 , 8 ]). We recently discovered an indirect q salvage pathway in which a queuine lyase (QueL) enzyme regenerates a preQ 1 intermediate that can then be used by canonical bTGT [ 7 ].…”
Section: Introductionmentioning
confidence: 99%